Przygotowanie nauczycieli do realizacji zadań wynikających z reformy systemu edukacji wdrażanej w Polsce od 1999 roku - Michalak, Joanna (Wydawnictwo Naukowe UAM Poznań, 2005)
The main objective of the doctoral dissertation was to analyse the process of changes implemented in the educational system in the years 1999–2002. The research work took place in 447 public and nonpublic teacher’s training institutions (123 public and 324 non-public institutions) and 5,892 public and non-public schools located in Poland. In the years 1999–2002 2,402 teachers (40.76%) and 447 directors of public and non-public teacher’s training institutions (40.04%) participated in the research. As a result, the problems of the research were answered and the hypotheses were confirmed.
Preparation of teachers for realisation of tasks imposed by the education system, reform implemented since 1999